Surgical Reconstruction of Mitral-Tricuspid Insufficiency Combined with Biatriomegaly in Marfan Syndrome - Popov, V. V.; Bolshak, O. O.; Boukarim, V. Zh.; Khoroshkovata, O. V.; Gurtovenko, O. M.; Novikov, E. V.; Попов, В. В.; Большак, О. О.; Букарім, В. Ж.; Хорошковата, О. В.; Гуртовенко, О. М.; Новіков, Євген Вячеславович (My University, 2023)
The aim. To analyze the results of introduction of complex reconstruction of the left and right parts of the heart in Marfan syndrome combined with mitral-tricuspid insufficiency, biatriomegaly and left ventriculomegaly. Materials and methods. As an example of this pathology, we present our observation. Female patient T., 24 years old, was examined and treated from 7/27/2022 to 8/17/2022 at the Department of Surgical Treatment of Acquired Heart Diseases of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with a diagnosis: Marfan syndrome. Stage IV mitral-tricuspid insufficiency. Biatriomegaly. High pulmonary hypertension. Permanent form of atrial fibrillation (for 10 years, since 2011). IIB heart failure with left ventriculomegaly with reduced left ventricular ejection fraction. NYHA functional class IV+. The patient underwent surgery in the following volume: mitral valve replacement with full preservation of the valve apparatus + tricuspid valve plasty with the imposition of a support ring + triangular plasty of the left atrium with its partial resection + resection of the right atrium. Results. Within 4 months after surgery, echocardiographic parameters showed significant decrease in the volume of the left ventricle, the diameters of both atria. In addition, there was a significant decrease in the level of N-terminal pro-brain natriuretic peptide and manifestations of heart failure. Conclusion. Taking into account the initial serious condition of the patient with Marfan syndrome and advanced mitral-tricuspid heart disease, left ventriculomegaly with a reduced left ventricular ejection fraction, biatriomegaly (left atrium 7.2 cm, right atrium 6.5 cm), permanent form of atrial fibrillation, complex reconstruction of the left and right parts of the heart leads to an improvement in the functional state of the myocardium. Мета – проаналізувати результати впровадження комплексної реконструкції лівих та правих відділів серця при синдромі Марфана в поєднанні з мітрально-тристулковою недостатністю, біатріомегалією та лівою вентрикуломегалією. Матеріали та методи. Як приклад цієї патології ми представили таке спостереження. Хвора Т., 24 років, перебувала на обстеженні та лікуванні з 27.07.2022 по 17.08.2022 у відділі хірургічного лікування набутих вад серця ДУ «Національний інститут серцево-судинної хірургії імені М. М. Амосова НАМН України» з діагнозом: синдром Марфана, мітрально-тристулкова недостатність IV ст.; біатріомегалія; висока легенева гіпертензія; постійна форма фібриляції передсердь (з 2011 року – 10 років); серцева недостатність IIB з лівою вентрикуломегалією та зниженою фракцією викиду лівого шлуночка; функціональний клас за NYHA IV+. Хворій виконано оперативне втручання в об’ємі: протезування мітрального клапана з повним збереженням клапанного апарату, пластика тристулкового клапана з накладанням опорного кільця, трикутна пластика лівого передсердя з його частковою резекцією, резекція правого передсердя. Результати. У терміни до 4 місяців після операції ехокардіографічні показники продемонстрували значне зменшення об’єму лівого шлуночка, діаметрів обох передсердь. Крім того, спостерігалося достовірне зниження рівня N-кінцевого пропептиду натрійуретичного гормону B типу (NT-proBNP), зменшення проявів серцевої недостатності. Висновки. Враховуючи початковий тяжкий стан хворої із синдромом Марфана та вираженою мітральнотристулковою вадою серця, лівою вентрикуломегалією зі зниженою фракцією викиду лівого шлуночка, біатріомегалією (ліве передсердя – 7,2 см і праве передсердя – 6,5 см), постійною формою фібриляції передсердь комплексна реконструкція лівих і правих відділів серця призводить до поліпшення функціонального стану міокарда. Прискіпливий диспансерний етап спостереження дасть змогу зменшити наслідки серцевої недостатності та тахіформи фібриляції передсердь.
Хірургічна реконструкція мітрально-тристулкової недостатності в поєднанні з біатріомегалією при синдромі Марфана
Keywords: cardiac surgery; atrial fibrillation; mitral-tricuspid malformation; left ventriculomegaly; cardiopulmonary bypass; sinus of Valsalva dilatation; кардіохірургічні втручання; фібриляція передсердь; ліва вентрикуломегалія; штучний кровообіг; дилатація синусів Вальсальви